Date rape among undergraduates in south-western Nigerian federal universities (2016)
The increasing number of date rapes occurring on University campuses and the need to decrease rape supportive attitudes point to the need for continued research on this field. Correlational survey design was adopted to examine the extent to which attitude towards date rape is associated with the respondents' emotional empathy, beliefs in rape myths and gender. Simple random sampling technique was adopted at three stages to draw one thousand two hundred and sixteen undergraduates comprising 645 (53.2%) males and 571 (46.8%) females from three Federal universities in South-western, Nigeria. Respondents' ages ranged from 16-32 years with mean of 18.21 years. College Date Rape Attitudes Survey (a=0.71); Beliefs about Women Scale (a=0.78) and Multi-Dimensional Emotional Empathy Scale (r=0.77) were adopted for data source. The results of the Product Moment Correlation Coefficient tested at 0.05 level of significance showed that while emotional empathy had inverse relationship with attitude towards date rape, beliefs in rape myths had positive relationship. Attitude towards date rape also differed on the basis of gender. It was concluded that psycho-demographic variables correlated with attitude towards date rape. Rape prevention programmes should therefore be broadened to incorporate strategies that could reverse erroneous rape myths as well as provide appropriate therapies to enhance the emotional empathy of University students.